2016
DOI: 10.13005/bbra/2033
|View full text |Cite
|
Sign up to set email alerts
|

Review the Effect of Internal Branding on Brand Performance in Shopping Centers in Tehran

Abstract: Recently branding through various communicative activities, as a means to an organization's success in providing promises of the brand, to respond to expectations set of customers, have been proposed. In an organization, strengthen the brand in the eyes of foreign customers need to strengthen brand position within the organization and among employees. In this study, to evaluate the effect of internal branding in shopping centers in Tehran on employee performance a model with a review of studies that have done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Consequently, while Castro et al (2004) did not note OCB as an influential factor on the customer perception, and as Pradhiptya (2013) argued OCB as an insignificant factor; our study revealed that especially three factors of OCB play an important role on the customers satisfaction. Palouzian and Hosseini (2016) noted that internal effectiveness, which refers to employee's satisfaction, citizenship behaviours and increased performance positively affects customer's perception about the organization, which is similar to our findings. According to conscientiousness dimension employees join meetings and represent extra efforts for the effectiveness of the organization to promote quality in the organization.…”
Section: B There Is a Positive And Significant Correlation Between Csupporting
confidence: 91%
See 4 more Smart Citations
“…Consequently, while Castro et al (2004) did not note OCB as an influential factor on the customer perception, and as Pradhiptya (2013) argued OCB as an insignificant factor; our study revealed that especially three factors of OCB play an important role on the customers satisfaction. Palouzian and Hosseini (2016) noted that internal effectiveness, which refers to employee's satisfaction, citizenship behaviours and increased performance positively affects customer's perception about the organization, which is similar to our findings. According to conscientiousness dimension employees join meetings and represent extra efforts for the effectiveness of the organization to promote quality in the organization.…”
Section: B There Is a Positive And Significant Correlation Between Csupporting
confidence: 91%
“…There are many previous studies that examined the impact of OCB on the customer satisfaction (Bilgin et al, 2015;Palouzian & Hosseini, 2016;Smith et al, 1983). However, the difference of this research is to empirically find this positive correlation in small-medium enterprises in a developing country, which we could not find similar studies in the literature.…”
Section: Research Work On the Relationship Between Ocb And Customer mentioning
confidence: 64%
See 3 more Smart Citations